Complications Associated with Retained Foreign Bodies from Infected Penile Implants: Proposal for the Use of an Implant‐Specific Checklist at the Time of Device Removal. (3rd April 2013) - Kava, Bruce R.; Burdick‐Will, Joshua
Abstract Introduction Infection of a penile prosthesis requires that all device hardware and associated foreign materials are removed, irrespective of whether a salvage procedure will be performed. Failure to remove all foreign bodies from the operative field may result in persistent infection, necessitating surgical intervention. Aim To review our experience with complications arising from retained foreign bodies following removal of an infected penile prosthesis. We highlight the clinical features that should raise suspicion of retained device‐associated materials, and also the role of imaging in evaluating these patients. Finally, a rational approach to prevent these occurrences is proposed with the implementation of an implant‐specific checklist. Methods Medical records and imaging studies of patients presenting to our center with retained foreign bodies following removal of an infected penile prosthesis were reviewed. Main Outcome Measures Clinical and radiologic details of each of these cases were abstracted, including patient demographics, presenting symptoms, characteristics of retained materials, bacterial cultures, treatment, and follow‐up. Results Presenting symptoms included: (i) persistent and relapsing drainage from cutaneous fistulae; (ii) cellulitis overlying an infected reservoir; (iii) persistent penile pain; and (iv) an asymptomatic individual requesting elective placement of a second implant. Infected foreign materials retrieved included: two rear‐tip extenders, a tubing connector, two infected reservoirs, and nonabsorbable mesh. Preoperative computerized tomography scan confirmed the presence and the location of all of these materials. Using this data, we propose using an implant‐specific checklist to insure removal of all device‐related foreign bodies when explanting an infected penile prosthesis. Conclusions A number of adverse sequelae may result from inadvertently leaving behind device‐related materials when an infected implant is removed. Ultimately it is the responsibility of the surgeon removing an infected implant to insure that all device components and associated materials are removed. We believe that implementing a two‐step implant‐specific checklist is a rational prevention strategy.